Penerapan Konsep Syariat Islam pada Perencanaan Gelanggang Olahraga Khusus Muslimat Di Kota Kendari - Yudisthessar Yudisthessar; Asri Andrias HB; Elvina Sari Taufiq (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2021)
Kendari City is a taqwa city. Kendari is one of the areas with the majority Muslim population, which is about 93,27% or around 345.778 inhabitantas are Muslims and Muslimates. Muslims are encouraged to exercise in order to get good benefits such as good physical and healthy body. The Kendari City Goverment has provided sport facilities and infrastructure such as teh City Park, but specifically some Muslimates are contrained by the law in Islamic Shari'a. In Islamic Law, Muslims and Muslimates are required to be devoted to Allah subhanahu wataala. The Muslimats really want to implement religious advice to exercise but also very much want to carry out religious advice to keep the aurats, keep their eyes down and avoid interfering with the opposite sex who are not mahromes. Because of these problems, Kendari City Muslimates need special facilities and infrastructure for sports. The method used in the planning this Gelanggang Olahraga Khusus Muslimat is descriptive method, observation dan study of literature from various literary sourches. From the Islamic Shari'a approach taken in planning, a shar'i sports arena design can be produced in Kendari City.